IMPROVING STUDENTS’ WRITING ACHIEVEMENT IN DESCRIPTIVE TEXT THROUGH EXAMPLES NON EXAMPLES TECHNIQUE AT THE SEVENTH GRADE STUDENTS OF MTS N PARE IN ACADEMIC YEAR 2016/2017 - ningrum, anis silvia (LENTERA : Jurnal Pendidikan dan Pengajaran; Vol 8 No 2 (2018): LENTERA : Jurnal Pendidikan dan Pengajaran, 2018)
Examples Non Examples technique is one of technique  in cooperative learning which uses picture and video related to the basic competence which makes students more active and creative to create or develop their idea about the subject that they notice. This study aimed tofind out whether examples non examples can improve students’ writing achievement in descriptive text at the seventh grade students of MTs N Pare in Academic Year 2016/2017 or not.The design used is Classroom Action Research (CAR).The data collection method were observation and field notes, test, and questionnaire. The subject of this research was the seventh grade in class VII-C with the total of students is35.The result shows that the students average in the first cycle is 78.00 and 71.43% students pass the success indicator while for the second cycle is 80.26 and 88.57% students pass the success indicator. Based on the means of the first cycle and second cycle, it shows that there is significant improvement from 78.00 to 80.26 and 71.43% to 88.57% students pass the indicator of success. Besides, students’ activities are more active and motivated in teaching learning process. Therefore, it is recomended that using examples non examples technique can improve students’ writing achievement especially in descriptive text.